EFFECTS OF NUTRIENT CONCENTRATION IN MULTI STAGE FEEDING OF THE GROWTH OF MICROALGAE Nannochloropsis sp. - Sriwuryandari, Lies; Priantoro, Ekaputra Agung; Sembiring, Tarzan (Teknologi Indonesia, 2017)
Renewable energy plays an important role for a sustainable future and the use of microalgae Nannochloropsis sp., as a potential source of biofuel due to its high lipid content, makes a good option. The nutrient found in the growth medium of microalgae have been found to affect cell synthesis, lipid synthesis, as well as its fatty acid profile. This study was conducted to observe the effects of the N-P concentration utilizing multistage feeding on the performance of Nannochloropsis sp. Sodium bicarbonate, urea, and sodium dihydrogen phosphate monohydrate were used as sources of C, N, and P for the microalgae. The nutrient feeding needed was calculated based on a molecular formula of microalgae(CO0.48H1.83N0.11P0.01) with a production target 1g.L-1 cell biomass. Element C is an iso-molar. The concentration of N- P varies: corresponding to the mol-fraction of the microalgae cell (as a control) and 10% excess. There were four levels of treatment: A (U0P0); B (U10P0); C (U0P10); and D (U10P10) with three replicants in the batch culture system. Nutrient feeding was conducted in three stages: I (40%); II (30%);and III (30%) and incubated in a neutral environment. Nannochloropsis sp. was able to grow well at a temperature of 24–35°C and an acidity level (pH) of 9.0–10.5. The culture (on the 21st day) produced DCW 0.93; 1.04; 0.86;1.12g.L-1, Chlorophyll-a 7.08; 7.62; 4.64; 6.85% DC, lipid 19.2; 15.5; 27.3; and 21.6% DC for treatments A; B;C; and D, respectively.The maximum lipid level resulted in an N deficiency and a P surplus (C). The lipids of the Nannochloropsis sp. composed of 66.0–81.1% saturated fatty acid which is suitable to be used as a biofuel.